Effect of Specimen Size and Shape on the Compressive Strength of High Strength Concrete - Malaikah, Alaa S. (Universiti Putra Malaysia Press, 2005)
The influence of specimen size and shape on the measured compressive strength was investigated for different high strength concrete mixes. Over 260 specimens from 30 high strength concrete mixtures were cast and tested. It was found, that on average, the ratio of the compressive strength of 150 x 300 mm cylinders to 150 mm cubes was 0.80; while for 100 x 200 mm cylinders to 150 mm cubes was 0.93. Also, on average, the ratio of the compressive strength of 150 x 300 mm cylinders to 100 x 200 mm cylinders was 0.86.